1983
DOI: 10.1073/pnas.80.23.7219
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent intervention by benzamide of carcinogen-induced neoplastic transformation and in vitro poly(ADP-ribosyl)ation of nuclear proteins in human fibroblasts.

Abstract: Human fibroblasts were subjected to nutritionally induced GI block, followed by release and subsequent entry into S phase, and exposed to nontoxic concentrations of carcinogens in early S phase. Cell transformation occurred as determined by early morphologic cell alterations, anchorage-independent colony formation, cell invasiveness, and augmentation of Ab 376 human malignancy-specific cell-surface antigenic determinant. Methylazoxymethanol acetate was the most potent transforming agent at doses that were nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…In contrast to these reports Kun et al (1983) found that ADPRT inhibitors block neoplastic transformation in human fibroblasts subjected to transforming but non-toxic doses of carcinogens. This finding has been extended by Borek et al (1984) (1) Cells are reported to possess both ADPribose dependent and -independent DNA repair pathways (Bohr & Klenow, 1981;Zwelling et al, 1982) and the independent pathway is suggested to be more rapid and error-prone than the dependent pathway.…”
Section: Adp-ribosylation and Neoplastic Transformationcontrasting
confidence: 71%
See 1 more Smart Citation
“…In contrast to these reports Kun et al (1983) found that ADPRT inhibitors block neoplastic transformation in human fibroblasts subjected to transforming but non-toxic doses of carcinogens. This finding has been extended by Borek et al (1984) (1) Cells are reported to possess both ADPribose dependent and -independent DNA repair pathways (Bohr & Klenow, 1981;Zwelling et al, 1982) and the independent pathway is suggested to be more rapid and error-prone than the dependent pathway.…”
Section: Adp-ribosylation and Neoplastic Transformationcontrasting
confidence: 71%
“…(2) Contrasting results may be due simply to the different concentrations of ADPRT inhibitor used (Kun et al, 1983 (Sims et al, 1983). Finally, it should be noted that there is no evidence that transformation results from inaccurate repair of strand breaks for any DNA-damaging agent.…”
Section: Adp-ribosylation and Neoplastic Transformationmentioning
confidence: 99%
“…PARP -/-fibroblasts and their PARP + counterparts, plated at 0.5x10 6 cells/plate, grew at the same rate. However, exposure (3 times weekly for 4 h during a period of 3 weeks) to the chemical carcinogens methylnitronitrosoguanidine (17 μM) or benzo(a)pyrene (2.6 μM), each dissolved in DMSO, converted PARP -/-fibroblasts to a malignant phenotype as assayed by colony formation (13). This carcinogeninduced malignant phenotype could not be reverted to the non-malignant cell type by incubation with 100 μM AI.…”
Section: Resultsmentioning
confidence: 99%
“…As pointed out by Cleaver et al [18], little is known about the effective concentrations of ADPRT inhibitors in intact ceils as opposed to permeable ones. Kun et al [28] observed that, in intact fibroblasts, 1 mM 3ABA in the culture medium resulted in a concentration of 10/zM inside the cell, which apparently increased, rather than inhibited, ADPRT activity. Furthermore, very little is known about the rate at which benzamides and nicotinamide are metabolized in intact cells, i.e.…”
Section: Discussionmentioning
confidence: 99%